PENGEMBANGAN MULTIMEDIA PADA MATERI STRUKTUR DAN FUNGSI ORGAN MANUSIA UNTUK SISWA KELAS XI SEKOLAH MENENGAH ATAS - Ahyar, Rania; Lufri, Lufri; Sumarmin, Ramadhan (Kolaboratif, 2014)
Biology is a subject that requires a lot of understanding of the concept. Because in learning, student are faced with many complicated concepts. To present complicated into simple consept and learning more meanigfull and easily understood by student, one way is through the medium of learning. This research aims to produce interactive multimedia on materials organ structure and function of human for students class XI SMA valid, practical, and effective. This research is the development research. This research use Plomp model development which stands for preliminary investigation phase, design phase, realization/construction phase, test, evaluation, and revision phase and also implementation phase. The data required to determine practicality was obtained from the observation and practicality sheet of the teacher and students. Then, to know the effectiveness of the data, it was obtained from the activity and the motivation of the students. The result could be seen from the validation average is 85 %. The percentage of practicality consists on: (1) practicality sheet of multimedia by the teacher is 91,6% , (2) practicality sheet of multimedia by the students is 90,25%. The effectiveness of multimedia can be seen from the students activities and motivated. The students activitiy sheet show average 90,4 % and the motivation all students to study is 92, 2%. In conclusion, the research on the multimedia on materials organ structure and function of human for the eleventh grade students of SMA has validity, practicality and effectiveness.